Multi-Walled Carbon Nanotubes Decorated with Guanidinylated Dendritic Molecular Transporters: An Efficient Platform for the Selective Anticancer Activity of Doxorubicin - Kyriaki-Marina Lyra; Archontia Kaminari; Katerina N. Panagiotaki; Konstantinos Spyrou; Sergios Papageorgiou; Elias Sakellis; Fotios K. Katsaros; Zili Sideratou (MDPI AG, 2021)
An efficient doxorubicin (DOX) drug delivery system with specificity against tumor cells was developed, based on multi-walled carbon nanotubes (MWCNTs) functionalized with guanidinylated dendritic molecular transporters. Acid-treated MWCNTs (oxCNTs) interacted both electrostatically and through hydrogen bonding and van der Waals attraction forces with guanidinylated derivatives of 5000 and 25,000 Da molecular weight hyperbranched polyethyleneimine (GPEI5K and GPEI25K). Chemical characterization of these GPEI-functionalized oxCNTs revealed successful decoration with GPEIs all over the oxCNTs sidewalls, which, due to the presence of guanidinium groups, gave them aqueous compatibility and, thus, exceptional colloidal stability. These GPEI-functionalized CNTs were subsequently loaded with DOX for selective anticancer activity, yielding systems of high DOX loading, up to 99.5% encapsulation efficiency, while the DOX-loaded systems exhibited pH-triggered release and higher therapeutic efficacy compared to that of free DOX. Most importantly, the oxCNTs@GPEI5K-DOX system caused high and selective toxicity against cancer cells in a non-apoptotic, fast and catastrophic manner that cancer cells cannot recover from. Therefore, the oxCNTs@GPEI5K nanocarrier was found to be a potent and efficient nanoscale DOX delivery system, exhibiting high selectivity against cancerous cells, thus constituting a promising candidate for cancer therapy.